AWARENESS OF CASSAVA PEEL UTILIZATION AS A FEEDSTUFF AMONG LIVESTOCK FARMERS IN OGBOMOSO ZONE OF NIGERIA - Taiwo Kayode OJEDIRAN; Victor DUROJAIYE; Rasheed Gbolagade ADEOLA; Janet Temitope OJEDIRAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
A well-constructed questionnaire was used to obtain data from livestock farmers through an interview schedule (n = 220) in five local government areas in Ogbomoso, Southwest Nigeria. This study assesses the characteristics of the livestock farmers, type of livestock kept, type of feed used, energy feedstuffs used in feed compounding, quantity of feed used daily, level of awareness of cassava peel utilization as livestock feedstuff, factors affecting the utilization of the identified potential energy feedstuff and constraints to the use of cassava peel as livestock feedstuffs. The survey results revealed that the respondents were mostly part time livestock farmers, middle aged men with less than 10 years farming experience, who kept majorly poultry and pigs amongst other livestock such as goat, sheep and mini-livestock. Compounded rations were commonly used with maize as the main energy feedstuff and the quantity of feed used daily indicated that they were small-scale farmers. Majority of the respondents were aware of the potential use of cassava peel as livestock feedstuff but indicated that availability of maize and sorghum, nutrient quality and seasonality influenced their utilization while ease of use and cost were factors also considered in Ogbomoso south and Ogo Oluwa for the use of sorghum. Cost and quantity were not of serious concern for use of whole cassava in livestock feed but storability, availability and seasonality were the major factors affecting its use as energy feedstuff while nutrient quality and rate of spoilage were constraints for the use of cassava peel. It can therefore be recommended that agricultural extensionist should work together with livestock nutritionists and reorient the farmers with available research outputs that had addressed the constraints of cassava peel usage for it to compete with maize as an energy feedstuff.